Estudo da radiação eletromagnética à luz da astronomia, no contexto das aulas de física, na 3ª série do ensino médio - Barreto, Davi Ferreira (2016)
This study was to investigate how the introduction of modern physics in high school, mediated by the study of astronomy, may favor the practice of teaching and learning of physics, from the perspective of the Theory of Meaningful Learning (TML), through the use of Sequence Didactic . In order to answer this question, we define the general objective: to analyze how the study of Astronomy, as a mediating element for the introduction of Modern Physics in High School, can favor the teaching and learning of Physics, from the perspective of SAT, in the 3ª Series. In order to achieve this purpose, we have drawn up the following specific objectives: to elaborate and evaluate the contribution of a didactic sequence on Electromagnetic Radiation, developed from the perspective of SAT, in the teaching and learning of Physics, in the 3ª High School Series; To introduce the study of Modern Physics mediated by Astronomy, with support of didactic sequence on Electromagnetic Radiation, from the perspective of SAT; To evaluate students' performance from the introduction of Modern Physics, mediated by the study of Astronomy, with the support of the Didactic Sequence from the perspective of SAT. From this perspective, it was developed in a senior high school class, in a public school from Santo Antonio de Jesus town, State of Bahia, and entitled "Knowing the Universe Through the Colors". The same had as its central theme Electromagnetic Radiations and constituted both an instrument and product of this research. The activities were designed in a way that would attract students' attention from the curiosity that usually astronomical phenomena cause in those who observe them. At the time they were arranged in ascending order in terms of complexity, and the correlation between them. This research has been prepared under qualitative and quantitative approach, from which have developed a descriptive understanding work of the investigated object. Finally, this study shows a very positive result of the methodology chosen and can say that the Didactic Sequence elaborate contributed to a meaningful learning of concepts covered in Modern Physics, mediated by Astronomy, enabling students to build knowledge that can serve as anchors for future concepts.